E-Governance and Digital Transparency in Combating Tax Evasion: A Comparative Analysis between Germany and Algeria - lamraoui, salim; Benlaharche, sarah (Journal of Research in Finance and Accounting, 2025)
This study presents an in-depth comparative analysis of the role of e-governance and digital transparency in mitigating tax evasion. It compares Germany, which serves as a global benchmark for a mature digital tax system, with Algeria, a developing country navigating a complex transition toward financial digitization. The study adopts a mixed-methods approach, combining qualitative institutional analysis with quantitative evaluation of key performance indicators, including e-filing adoption rates, VAT gap trends, and digital infrastructure metrics. Through a detailed examination of Germany’s highly integrated "ELSTER" system and Algeria’s emerging "Jibayatic" system, the study moves beyond surface-level descriptions to diagnose a profound “digital maturity gap.” This gap is shown to arise from disparities in technological infrastructure, legal and regulatory frameworks, data system integration, and deeply rooted sociocultural factors tied to tax morale and digital trust. The study concludes that bridging this gap requires more than technological investment; it calls for a comprehensive, long-term strategy centered on institutional reform, legal modernization, and the rebuilding of public trust. It also puts forward actionable recommendations for Algerian policymakers to effectively steer this complex, multi-phase transformation.